Simplified numerical analysis of bond degradation of FRP-masonry systems for durability purposes - Ghiassi, Bahman (2011)
Fiber Reinforced Polymers have become a popular material for external strengthening of masonry structures in the last years, but still further investigations are needed in order to develop appropriate design procedures. Investigating the behaviour and performance of retrofitted masonry elements with FRP composite sheets requires considering different mechanisms and issues. Among them, the most important is the bond between FRP and substrate due to its function in transferring the stresses from the FRP sheets to the structure. Hence, conducting experimental and numerical studies for understanding the bond and its degradation mechanism due to environmental exposure is a critical subject in predicting the performance of strengthened structures. As the available information on the durability of bond in FRP retrofitted masonry elements is still rare, conducting extensive experimental and numerical studies for characterizing this phenomenon is an important issue. This paper presents a simple degradation model into an available interface model for investigating the bond degradation in retrofitted masonry elements. For this reason, at first the interface model is calibrated with the experimental tests performed at University of Minho, and then the degradation of the bond is implemented in this model through a simplified approach.